Role of a geodatabase to assess the distribution of plants of conservation interest in a large protected area: A case study for a major national park in Italy. (4th July 2018) - Viciani, D.; Geri, F.; Agostini, N.; Gonnelli, V.; Lastrucci, L.
Abstract: We use a geodatabase to investigate the distribution patterns of an important subset of floristic reports recorded for the Parco Nazionale delle Foreste Casentinesi, Monte Falterona, Campigna in the northern Apennines, Italy. This database was analysed using spatial statistical techniques and a digital elevation model. Significant relationships between species presence, sampling effort and species richness were then analysed in relation to topographical variables and to an existing vegetation map. Report-based rarefaction techniques were used to compare areas having different numbers of species recorded. Overall, the analysis shows that some areas of the park are richer in species of conservation interest than others, and that these have been more intensely investigated. Meanwhile, for other areas, botanical knowledge is scarce or even absent. This has led to clustering and redundancy of floristic data in some areas. The study confirms that the existence of a complete and up-to-date geodatabase creates a valuable resource which enables information gaps to be bridged. Such gaps often exist in biological databases for rare and narrowly distributed species. The wider application of these analyses should also give useful indications of how the incidences of these species of conservation interest are associated with particular environmental variables.